On Interaction between the City and the Language(s): Individual to Society / Bireyden Topluma: Kent ve Dil İlişkisi Üzerine - Guven, Seda; Tekdemir, Goklem (The City's Language / Şehrin Dili / Langues de la ville, 2021)
Cities are places where the relationship between individual and society can be explored in interaction with spaces. The chapters in this book focus on how cities and languages are related. It's goal is to hear the languages the city speaks by attending to the individuals residing there, their cultural backgrounds and the impact of the symbols, representations, ideologies and policies that they produce, consume and are exposed to while living in the cities. The collection of chapters here reveals the social role of language, urban identities, the relationship of urban identities with consumerism and how lifestyles are transformed due to domestic and external immigration, urban life politics, media presentations and ideologies.